2014
DOI: 10.1039/c3dt53266f
|View full text |Cite
|
Sign up to set email alerts
|

Facial triad modelling using ferrous pyridinyl prolinate complexes: synthesis and catalytic applications

Abstract: oxidant limiting conditions. The complexes were shown to be especially active in the epoxidation of styrene type substrates (styrene and trans-beta-methylstyrene). In the best case, complex [Fe(6-MePyProNH 2 )Cl 2 ] (15) allowed for 65% productive consumption of hydrogen peroxide toward epoxide and benzaldehyde products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…[26,27] Our group recently reported the first example of an oxidation catalyst with a single chiral facial N,N,Oligand: the [Fe(PyProMe)Cl 2 ] complex ( Figure 1). [28] The use of this and related iron complexes resulted in good turnover numbers (up to 50) in the epoxidation of olefins, but no significant enantioselectivity was obtained. [28,29] However, the structure of this complex is very flexible and the chiral pyridinyl prolinate ligand easily isomerizes between facial and meridional coordination modes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[26,27] Our group recently reported the first example of an oxidation catalyst with a single chiral facial N,N,Oligand: the [Fe(PyProMe)Cl 2 ] complex ( Figure 1). [28] The use of this and related iron complexes resulted in good turnover numbers (up to 50) in the epoxidation of olefins, but no significant enantioselectivity was obtained. [28,29] However, the structure of this complex is very flexible and the chiral pyridinyl prolinate ligand easily isomerizes between facial and meridional coordination modes.…”
Section: Introductionmentioning
confidence: 98%
“…[28] The use of this and related iron complexes resulted in good turnover numbers (up to 50) in the epoxidation of olefins, but no significant enantioselectivity was obtained. [28,29] However, the structure of this complex is very flexible and the chiral pyridinyl prolinate ligand easily isomerizes between facial and meridional coordination modes. Many other studies resulted in the isolation of bis-ligand complexes; for example, Burzlaff et al found that the bis(pyrazolyl)acetate ligand (bdmpzaH) affords FeL 2 type and Figure 1.…”
Section: Introductionmentioning
confidence: 98%
“…The introduction of the pyridine pendant fragment was accomplished by deprotonation of the acidic methylene fragment of 3 followed by nucleophilic substitution on a freshly prepared 2‐picolyl chloride solution . The latter was released from the hydrochloride adduct upon salt washing with an aqueous NaHCO 3 solution (pH = 8) followed by extraction in organic solvents . The HCl‐free 2‐picolyl chloride was used immediately in the nucleophilic substitution with 3 – Na + without any further purification.…”
Section: Resultsmentioning
confidence: 99%
“…Infrared absorption (IR) measurements have been conducted to confirm the existence of ILs inside the pores of Cu-BTC. The FT-IR spectra of [EMIM][OTf]@Cu-BTC and pure IL (Figure 3) show IR bands around 1026, 1058, and 1135 cm −1 , which were exclusively found in the supported ionic liquid and are due to the SO 3 vibration of the OTf − moieties (1026 cm −1 ) and CF 3 asymmetric vibrations, respectively [16]. In the case of the [EMIM][BF 4 ]@Cu-BTC composite, the presence of the IL is discernible by the appearance of the band at 1168 cm −1 ascribed to the C–H in-plane vibration of the EMIM + cation and another band at 1037 cm −1 due to the B–F vibrations in the BF 4 − anion (Figure S1 in Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%